2019
DOI: 10.3168/jds.2018-14567
|View full text |Cite
|
Sign up to set email alerts
|

Reducing methane production with corn oil and calcium sulfate: Responses on whole-animal energy and nitrogen balance in dairy cattle

Abstract: The addition of fat and calcium sulfate to diets fed to ruminants has resulted in a reduction in methane production, but the effects on energy balance have not been studied. A study using indirect calorimetry and 16 multiparous (8 Holstein and 8 Jersey; 78 ± 15 d in milk; mean ± standard deviation) lactating dairy cows was conducted to determine how mitigating methane production by adding corn oil or calcium sulfate to diets containing reduced-fat distillers grains affects energy and nitrogen balance. A replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Methane production represents an energetic loss for the ruminant. Thus, reducing it could result in the repartition of more energy toward production (Judy et al, 2019). Bell et al (2010) observed a 12% difference in CH 4 intensity (g of CH 4 /kg of milk) between control and selected (for kg of milk fat and protein production) genetic lines, whereby genetically selected cows partitioned more of their nutrient intake toward milk production and less to CH 4 .…”
Section: Correlation Among Components Of Feed Efficiencymentioning
confidence: 99%
“…Methane production represents an energetic loss for the ruminant. Thus, reducing it could result in the repartition of more energy toward production (Judy et al, 2019). Bell et al (2010) observed a 12% difference in CH 4 intensity (g of CH 4 /kg of milk) between control and selected (for kg of milk fat and protein production) genetic lines, whereby genetically selected cows partitioned more of their nutrient intake toward milk production and less to CH 4 .…”
Section: Correlation Among Components Of Feed Efficiencymentioning
confidence: 99%
“…Sulfur-containing amino acids shifted H 2 to a different hydrogen sink, increasing dH 2 S production rather than CH 4 production. This occurs under standard gut conditions because sulfidogenic bacteria have a higher affinity for H 2 utilization than methanogens, suggesting thermodynamically methanogenesis is less favored than sulfate reduction ( Van Zijderveld et al, 2010 ; Judy et al, 2019 ; Lan and Yang, 2019 ; Teklebrhan et al, 2020 ). Because sulfur-reducing microbes use sulfur as an electron sinker or acceptor, and the reduced forms of sulfur H 2 S is a metabolic end-product of fermentation from these microorganisms and noticed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to reduce the level of crude protein (CP) in ruminant diets with the supplementation of limiting amino acids such as methionine and lysine, to improve the number of metabolizable amino acids; and decrease nitrogen losses, feed costs, and greenhouse gas emissions without adverse effect on animal performance ( Sinclair, 2014 ; Guyader et al, 2016 ). It has been shown that dietary supplements with high sulfate could shift H 2 toward energetically advantageous pathways away from methanogenesis and reduce methane emissions and yield ( Judy et al, 2019 ; Lan and Yang, 2019 ; Teklebrhan et al, 2020 ). For instance, a sulfur-rich corn gluten diet decreased dissolved hydrogen (dH 2 ) and methane (dCH 4 ), while increasing dissolved hydrogen sulfur (dH 2 S) which was associated with reduced methanogenesis in goats fed on corn meal ( Teklebrhan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…At 1700 h daily, tubs were removed, weight was recorded, and 10% of total urine collection was retained and stored at 2.8 °C until further analysis. Urine was thawed and boiled to reduce water content prior to further analysis ( Judy et al, 2019 ). Beakers filled with urine were placed into a boiling water bath (Ankom Technology, Macedon, NY) underneath a hood until urine reached consistency of a paste.…”
Section: Methodsmentioning
confidence: 99%